Mossbauer spectroscopy study of iron oxide nanoparticles obtained by spray pyrolysis - Marques, R. F. C. [UNESP]; Rodriguez, A. F. R.; Coaquira, J. A. H.; Santos, J. G.; Garg, V. K.; Jafelicci, M. [UNESP]; Ribeiro, S. J. L. [UNESP]; Verelst, M.; Dexpert-Ghys, J.; Morais, P. C.; Kuzmann, E.; Lazar, K. (Springer, 2009)
Mossbauer spectroscopy was used in this study to investigate magnetite nanoparticles, obtained by spray pyrolysis and thermal treatment under H-2 reduction atmosphere. Room temperature XRD data indicate the formation of magnetite phase and a second phase (metallic iron) which amount increases as the time of reduction under H-2 is increased. While room temperature Mossbauer data confirm the formation of the cubic phase of magnetite and the occurrence of metallic iron phase, the more complex features of 77 K-Mossbauer spectra suggest the occurrence of electronic localization favored by the different crystalline phase of magnetite at low temperatures which transition to the lower symmetry structure should occur at T similar to 120 K (Verwey transition).
Keywords: Magnetite; Hematite; Spray pyrolysis; Mossbauer spectroscopy